Relationship of lower body explosive strength to acceleration velocity in U17 players (Impetus, 2026)
To investigate the relationship between explosive strength and speed is essential to improve their performance and provide a deeper understanding of the different strategies and approaches that can be implemented in the training field. To determine the relationship of lower body explosive strength with acceleration speed in U17 soccer players. Adopting a positivist approach and using a quantitative design of correlational scope, a sample of 21 male soccer players from the department of Sucre-Colombia was examined. The 30-meter speed test and the SJ, CMJ and ABK jumps were carried out. Significant correlations were found (p
Keywords: Soccer; Acceleration speed; Explosive strength; Bosco test